Precise prediction of optical responses of all types of liquid crystal displays by behavioral models. Issue 1 (20th March 2013) - Kim, Jong‐Man; Cho, Youngmin; Kim, Jongbin; Lee, Seung‐Hyuck; Kim, Kwangjoon; Lee, Seung‐Woo
Abstract We propose a behavioral circuit model to estimate transient optical responses of an active‐matrix liquid crystal display (AMLCD). We apply it to twisted‐nematic, patterned vertical alignment, and in‐plane switching AMLCDs to verify our model's universality. To obtain more accurate simulation results, we propose a method to obtain the capacitance–voltage data from natural optical responses. We describe the behavior of all types of AMLCDs by using an analog hardware description language, Verilog‐A. We simulate the AMLCD panels by importing the behavioral circuit model in a circuit simulator, Smart‐SPICE. The simulation results of the transient optical responses were almost identical to the measurement ones regardless of liquid crystal modes.